The Hybrid Simplified Kalman Filter for Adaptive Feedback Cancellation - Albu, F.; Tran, L.; Nordholm, Sven (2018)
© 2018 IEEE. Numerous adaptive feedback cancellation (AFC) algorithms are used in open-fitting and in-ear hearing aid devices (HADs) in order to avoid the possible annoying howling sounds. Recently, a hybrid AFC (H-AFC) scheme that shortened the recovering time from howling was proposed. It consists of a switched combination adaptive filter controlled by a stability detector that chooses either the standard normalized least mean squares (NLMS) algorithm or the prediction-error method (PEM) NLMS algorithm. In this paper a hybrid simplified Kalman filter (H -SKF) that uses a modified stability detector and a switch between NLMS and (PEM) SKF algorithms is proposed. It is shown that the proposed approach improves the convergence properties and shortens the howling periods for both speech and music signals compared with the hybrid NLMS (H-NLMS) algorithm.